Influence of Sociocultural Practices on Food and Nutrition Security in Karamoja Subregion of Uganda - Muggaga, C.; Ongeng, D.; Mugonola, B.; Okello-Uma, I.; Kaaya, N. A.; Taylor, D. (Ecology of food and nutrition, 2017)
The study determined the influence of sociocultural practices on food and nutrition security of children and women in Karamoja subregion, located in northeastern Uganda. Sixteen focus group discussions were conducted among 133 participants. Data were analyzed using qualitative content analysis. Findings indicate that cultural norms, myths, and taboos restrict consumption of animal-sourced foods and some green vegetables by women. Sociocultural practices promoted prelacteal feeding, affecting the implementation of World Health Organization’s recommendations for exclusive breast feeding. In conclusion, sociocultural practices influence food and nutrition security, exposing women and children to the risk of malnutrition and associated consequences.
Keywords: Child nutrition; ethnicity; exclusive breastfeeding; maternal nutrition